Aquaponics Cultivation of Ipome Aquatica and the Peasant Financial Income of Cirata Cistern - Abel Gandhy (Shirkah: Journal of Economics and Business, 2016)
The research paper analyzes the financial income of a poor community living around the Cirata cistern, in West Java, Indonesia, before and after the community employed the aquaponics strategy of planting ipomoea aquatica. Data are gathered from observation, interviews and statistical analysis of the incomes of community members. In addition, analysis of the data applies Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PP). The findings clearly demonstrate an increased annual income of more than 1.117.296 rupiah among those community members using the aquaponics strategy. Once the community has adjusted to professionally implementing this aquaponics strategy, it would be practically useful to invite investors to invest their capital to develop this area.Â Keywords: aquaponics, financial income, West Java, internal rate of return, payback periodÂ Â